On Automata Accepting Biordered Set Languages and its Properties - Kumar, P. Ramesh; Nainan, Jino (Communications in Mathematics and Applications, 2021)
Here we introduce the notion of finite state machines which accepts biordered set languages termed as nice automata. We begin by a basic type of automata termed as elementary automata which accepts elementary languages and give a characterization for the same. By considering the biordered set languages recognized by finite monoids we call them as finitely bsl, we see that the language L is finitely bsl if and only if there exist a nice automaton A such that L = L(A). Also we see that product is the only operation which is closed in the class of nice automata.